Languages are efficient, but for whom? - Trott, Sean; Bergen, Benjamin (Cognition, 2022)
Human languages evolve to make communication more efficient. But efficiency creates trade-offs: what is efficient for speakers is not always efficient for comprehenders. How do languages balance these competing pressures? We focus on Zipf's meaning-frequency law, the observation that frequent wordforms have more meanings. On the one hand, this law could reflect a speaker-oriented pressure to reuse frequent wordforms. Yet human languages still maintain thousands of distinct wordforms, suggesting a countervailing, comprehender-oriented pressure. What balance of these pressures produces Zipf's meaning-frequency law? Using a neutral baseline, we find that frequent wordforms in real lexica have fewer homophones than predicted by their phonotactic structure: real lexica favor a comprehender-oriented pressure to reduce the cost of frequent disambiguation. These results help clarify the evolutionary drive for efficiency: human languages are subject to competing pressures for efficient communication, the relative magnitudes of which reveal how individual-level cognitive constraints shape languages over time.